1995
DOI: 10.1101/gad.9.5.509
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking ADPRT and poly(ADP-ribosyl)ation develop normally but are susceptible to skin disease.

Abstract: Poly(ADP-ribosyl)ation is catalyzed by NAD + :protein(ADP-ribosyl)transferase (ADPRT), a chromatinassociated enzyme which, in the presence of DNA breaks, transfers ADP-ribose from NAD + to nuclear proteins. This post-translational modification has been implicated in many fundamental processes, like DNA repair, chromatin stability, cell proliferation, and cell death. To elucidate the biological function of ADPRT and poly(ADP-ribosyl)ation in vivo the gene was inactivated in the mouse germ line. Mice homozygous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
508
3
3

Year Published

1995
1995
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 740 publications
(533 citation statements)
references
References 48 publications
(45 reference statements)
19
508
3
3
Order By: Relevance
“…We attributed this e ect to the co-regulated inhibition of the expression of PARP, an enzyme implicated in DNA-repair (Satoh and Lindahl, 1992). This suggestion is consistent with ®ndings by others that PARP levels are not rate limiting for the proliferation of normal (undamaged) cells and that downregulation of PARP expression results in increased cell susceptibility to DNA-damaging treatments (Ding et al, 1992;Wang et al, 1995;KuÈ pper et al, 1995;Schreiber et al, 1995). Another explanation may involve the potential role of the ETS protein itself in the radiation response of EWS cells.…”
Section: Inhibition Of Ets1 Expression Enhances Growth Retardation Ofsupporting
confidence: 90%
“…We attributed this e ect to the co-regulated inhibition of the expression of PARP, an enzyme implicated in DNA-repair (Satoh and Lindahl, 1992). This suggestion is consistent with ®ndings by others that PARP levels are not rate limiting for the proliferation of normal (undamaged) cells and that downregulation of PARP expression results in increased cell susceptibility to DNA-damaging treatments (Ding et al, 1992;Wang et al, 1995;KuÈ pper et al, 1995;Schreiber et al, 1995). Another explanation may involve the potential role of the ETS protein itself in the radiation response of EWS cells.…”
Section: Inhibition Of Ets1 Expression Enhances Growth Retardation Ofsupporting
confidence: 90%
“…Thus, under these conditions, quiescent control cells are induced to proliferate and go through a round of the cell cycle, but not the PARP-depleted antisense cells. To determine whether depletion of PARP by gene disruption similarly blocks reentry of cells into S phase, we studied immortalized ®broblasts that were derived from wild-type (control) and PARP knockout (PARP7/7) mice (Wang et al, 1995). These PARP7/7 cells were previously con®rmed to be devoid of detectable PARP and poly(ADP-ribose) by immunoblot analysis with the corresponding antibodies (Simbulan-Rosenthal et al, 1998b).…”
Section: Resultsmentioning
confidence: 99%
“…While certain strains of PARP knockout mice are viable and fertile, primary ®broblasts derived from these animals exhibit proliferation de®ciencies in culture (de Murcia et al, 1997;Wang et al, 1995). Thus, although both DNA replication and di erentiation occur in these animals in the absence of PARP, isolated cell systems may show more profound e ects of the lack of this enzyme that are not apparent in the animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This data is consistent with the involvement of an ICE-like protease in PARP proteolysis. However the significance of PARP proteolysis in apoptosis is unclear as a PARP knockout mouse developed normally [35]. This suggested that apoptosis probably does not have an absolute requirement for proteolysis of PARP but rather that it may be a consequence of cell death.…”
Section: Discussionmentioning
confidence: 99%